Ultra-High-Energy Cosmic Rays Accelerated by Magnetically Dominated Turbulence - Luca Comisso; Glennys R. Farrar; Marco S. Muzio (The Astrophysical Journal Letters)
Ultra-high-energy cosmic rays (UHECRs), particles characterized by energies exceeding 10 ^18 eV, are generally believed to be accelerated electromagnetically in high-energy astrophysical sources. One promising mechanism of UHECR acceleration is magnetized turbulence. We demonstrate from first principles, using fully kinetic particle-in-cell simulations, that magnetically dominated turbulence accelerates particles on a short timescale, producing a power-law energy distribution with a rigidity-dependent, sharply defined cutoff well approximated by the form ${f}_{\mathrm{cut}}\left(E,{E}_{\mathrm{cut}}\right)={\rm{sech}} \left[{(E/{E}_{\mathrm{cut}})}^{2}\right]$ . Particle escape from the turbulent accelerating region is energy dependent, with t _esc ∝ E ^− ^δ and δ ∼ 1/3. The resulting particle flux from the accelerator follows ${dN}/{dEdt}\propto {E}^{-s}{\rm{sech}} \left[{(E/{E}_{\mathrm{cut}})}^{2}\right]$ , with s ∼ 2.1. We fit the Pierre Auger Observatory’s spectrum and composition measurements, taking into account particle interactions between acceleration and detection, and show that the turbulence-associated energy cutoff is well supported by the data, with the best-fitting spectral index being $s={2.1}_{-0.13}^{+0.06}$ . Our first-principles results indicate that particle acceleration by magnetically dominated turbulence may constitute the physical mechanism responsible for UHECR acceleration.